Representing ECM composition and EMT pathways in gastric cancer using a new metastatic gene signature - Albano, Francesco; Russi, Sabino; Laurino, Simona; Mazzone, Pellegrino; Di Paola, Giuseppina; Zoppoli, Pietro; Amendola, Elena; Balzamo, Chiara; Bartolo, Ottavia; Ciuffi, Mario; Ignomirelli, Orazio; Sgambato, Alessandro; et al. (Frontiers in Cell and Developmental Biology, 2024)
Gastric cancer (GC) is an aggressive and heterogeneous malignancy in which cancer cells start to invade through the stomach (stage I) until they metastasize to distant organs (stage IV), becoming lethal. We compared the gene expression profiles of 719 GC patients in seven different public datasets and identified a gene signature (APOD, COL1A2, FSTL1, GEM, LUM, and SPARC) characterizing stage IV disease, which is related to extracellular matrix (ECM) organization and the epithelial-tomesenchymal transition (EMT). We recreated a simplified ECM in vitro via the gene signature. This model recapitulates the signaling of metastatic disease, influencing the microenvironment and promoting cell invasion, triggering EMT.Overall, we identified a gene signature able to group Stage I GC patients at higher risk that is useful for the management of Stage I patients. Furthermore, our experimental model could be useful for further dissecting the molecular signaling that underlies the metastatic spread of cancer cells.